“Análisis de la política del país de Holanda, para la protección, manejo y cuidado de la fauna urbana y la regulación en el GAD municipal del cantón Paltas”. - Sánchez Neira, Wellington Freddy (2024)
The present research work entitled "Analysis of the policy of the country of Holland, for the protection, management and care of urban fauna and regulation in the municipal Gad of the Paltas canton", has the purpose of guaranteeing the protection and control of the Urban fauna is regulated directly by the Municipal Autonomous Decentralized Governments (GADS), who follow guidelines established by different ministries, in order to implement public policies and programs that promote responsible pet ownership, sterilization and vaccination, as well as awareness. and active community participation. This will improve coexistence between urban fauna and inhabitants, and will contribute to maintaining a healthy and balanced environment for everyone. Here is the importance of analyzing the conservation of nature and respect for the biodiversity of our pets, this drives us to start an environmental culture where urban fauna, which accompanies us day after day, is involved. Article 140 of the Environmental Organic Code stipulates that urban fauna includes domestic animals that live in public spaces and green areas, which can generate different risks of acquiring contagious diseases that put humans at risk, that is why it is known that in the Catacocha parish, Paltas Canton, Province of Loja, there is no correct legal regulation (ordinance) that regulates and controls urban fauna, guaranteeing principles of animal welfare. The type of research is legal and doctrinal, in addition the necessary methods were used such as: inductive, deductive, analytical, exegetical, maieutic, comparative, statistical and also synthetic. And regarding field work, techniques such as surveys and interviews were applied from which the criteria of professionals could be obtained, in order to verify the problem posed and suggest a proposal as a solution.